Cleavage anisotropy of boron doped cracks in crystalline silicon. (November 2022) - Liu, B.; Zhang, Y.A.; Li, Y.J.; Wang, X.F.; Yue, Y.J.
Abstract: We demonstrate a density functional theory (DFT) research on the modified cleavage anisotropy in crystalline silicon (c-Si) by impurity boron (B). Three representative cracks, (1 1 1)[1 1¯ 0], (1 1 0)[0 0 1] and (1 1 0)[1 1¯ 0] with B atoms located at the crack front, are investigated. The anisotropic behaviors are characterized by the stability (or lattice trapping) of the cracks subjected to Mode I load. Results show that B performs rather inconsistently in different cracks. The upper lattice trapping limit of the B implanted (1 1 1)[1 1¯ 0] crack is largely increased, indicating that it is more difficult to propagate. This is principally because B promotes the transition of the fracture surface from Haneman reconstruction to Pandey reconstruction which is structurally more stable. In comparison, the B-doped (1 1 0) [0 0 1] crack propagates more easily because B is energetically favored at the valley site of the reconstructed (1 1 0) fracture surface, thus making the SiB bond at the crack front easier to break. As for the (1 1 0) [1 1¯ 0] crack, B weakens the neighboring SiSi bonds, consequently inclines the propagation from (1 1 0) plane to adjacent (1 1 1) plane. Highlights: The cleavage anisotropy of c-Si modified by impurity B is captured by DFT. The (1 1 1)[1 1¯ 0] crack is stabilized by B. The (1 1 0)[0 0 1] crack becomes less stable when introduced with B. B promotes the propagation inclination of the (1 1 0)[1 1¯ 0] crack.